2006
DOI: 10.1021/jp057180p
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of Solid Surfaces Modified by Langmuir−Blodgett Monolayers Using Sum-Frequency Vibrational Spectroscopy and X-ray Photoelectron Spectroscopy

Abstract: Langmuir-Blodgett (LB) monomolecular layers of alkylhydroxamic acids and alkylphosphonic acids on copper and iron substrates have been studied by X-ray photoelectron spectroscopy (XPS) and sum-frequency vibrational spectroscopy. According to the XPS results, the structures of the hydroxamic acid and phosphonic acid Langmuir-Blodgett films are very similar: the thickness of the layer of the hydrocarbon tails is typically 1.9-2.1 nm, while the layer of headgroups is about 0.3-0.35 nm thick. The tilt angle of the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
46
0
1

Year Published

2011
2011
2017
2017

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 60 publications
(51 citation statements)
references
References 84 publications
4
46
0
1
Order By: Relevance
“…Note that similar shifts (around 0.8 eV) have also been reported for the grafting of phosphonic acids on transition metal oxide surfaces. 49 Figure 5a−c shows XPS C 1s region of bare NRs and of PPA and TDPA functionalized NRs (PPA-NRs and TDPA-NRs). The C 1s peak of bare NRs is a convolution of two components.…”
Section: ■ Experimental Sectionmentioning
confidence: 99%
“…Note that similar shifts (around 0.8 eV) have also been reported for the grafting of phosphonic acids on transition metal oxide surfaces. 49 Figure 5a−c shows XPS C 1s region of bare NRs and of PPA and TDPA functionalized NRs (PPA-NRs and TDPA-NRs). The C 1s peak of bare NRs is a convolution of two components.…”
Section: ■ Experimental Sectionmentioning
confidence: 99%
“…Phosphonic acid nanolayers have also been studied (1H,1H,2H,2H-perfluorodecyl phosphonic acid, 1-octyl-, decyl-and octadecyl phosphonic acids) (Hoque, 2009, Raman, 2010, Telegdi, 2005b, Rigó, 2005, Keszthelyi, 2006. This work showed that with increasing carbon length, the compactness of the surface SAM layer improves and the anticorrosion and antifouling effect significantly increases.…”
Section: Phosphonic Acidsmentioning
confidence: 99%
“…SFS is an efficient technique for obtaining information about the molecular level order of the prepared nanofilm, which is directly correlated with its performance as a protective layer (Keszthelyi, 2006). SFS is based on the nonlinear optical phenomenon which occurs when a light beam with a fixed wavelength in the visible part of the spectrum interacts with one at infrared wavelength which scans the surface.…”
Section: Study and Characterization Of Nanolayersmentioning
confidence: 99%
See 1 more Smart Citation
“…The thickness and structure of OPA layer was studied in detail elsewhere (Keszthelyi et al 2006). Briefly, the mechanism of assembly is Table 3 and 4, and shape of O 1s peaks, not shown here).…”
Section: Competitive Plu and Protein Adsorption Examined By Xps And Tmentioning
confidence: 99%